Fiscal multipliers with financial fragmentation risk and interactions with monetary policy - Matthieu Darracq Pariès; Georg Müller; Niki Papadopoulou (European Central Bank (ECB), 2020)
We quantify the size of fiscal multipliers under financial fragmentation risk and demonstrate how non-standard monetary policy can support the macroeconomic transmission of fiscal interventions. We employ a DSGE model with financial frictions whereby the interplay of corporate, banks and sovereign solvency risk affect the transmission of fiscal policy. The output multiplier of fiscal expansion is found to be significantly dampened by tighter financial conditions in case households are less certain about implicit and explicit state-guarantees for the banking system, or banks are weakly capitalized and highly exposed to the government sector. In this context, we show that central bank asset purchases or liquidity operations designed to ensure favourable bank funding conditions can restore fiscal multipliers.
Keywords: E44; E52; E62; 330; DSGE models; fiscal stabilization; sovereign risk; sovereign-bank nexus